Identifikasi dan Prevalensi Ektoparasit pada Ikan Kerapu Tikus (Cromileptes altivelis) di Karamba Jaring Apung Unit Pengelola Budidaya Laut Situbondo [ Identification And Prevalence Of Ectoparasites In Grouper (Cromileptes altivelis) At Floating Net Cage Of Marineculture Management Unit Situbondo] - Sri Subekti; Rahayu Kusdarwati; Ferlyn Hendra Wiyatno (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Grouper is a fish that lives in coral reefs, which is the internationally known as groupers or coral reef fishes. These fish have high economic value and potential to be developed in Indonesia. Grouper traded alive, the price is relatively high. The price of grouper at the level fishermen to reach US 20 (Rp 200,000, -) for each kilogram.These fish are exported mainly to Hong Kong with high price. Development of grouper aquaculture in floating net a viable alternative to overcome the increasing production of marine fisheries. The problem that often inhibiting fish culture is the diseases emergence, among others, caused by the parasites. The emergence of the disease is the result of interaction between environmental conditions that dont support the cultivation of their life inside, fish (host) that are sensitive and the presence of parasites. Uncontrolled environmental conditions there for the fish become stressed with poor immune systems, and facilitate pathogenic substance attacked hosts. This study aimed to the identify ectoparasites that attacked the grouper (Cromileptes altivelis) in floating net cages and to determine the prevalence rate of ectoparasites that attacked the grouper (Cromileptes altivelis) in floating net cages. The method of this study was descriptive method. Samples were taken with body length between 15-20 cm and four months old from the floating net. The main parameters observed in this study was identification of ectoparasites that attacked the grouper (Cromileptes altivelis) in floating net cages and prevalence rates for each of ectoparasites. While the supporting parameters were that water quality value in floating net cages as follow temperature, pH and salinity were measured during sampling activities. The results showed that of 60 samples were taken from four plots of floating net cages, 21 fish infected with ectoparasites positive. 17 positive fishes infected Pseudorhabdosynochus sp., one sample positive infected Benedenia sp. 3samples positive infected fish Neobenedenia sp. The ectoparasites prevalence of from cages 1, 2, 3 and 4 of 26.66%, 33.33% , 53.33% and 26.66% The suggestion of this study is cleanness improvement of floating net cage management to reduce ectoparasites infectation.